1970
DOI: 10.2136/sssaj1970.03615995003400020018x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Transformations in a Column with a Controlled Water Table

Abstract: The relation of dissolved oxygen, soluble carbon, and redox potential to the movement of nitrate in soil columns and into submerged tile lines was studied. Columns 300 cm long were drained at depths of 180, 240, or 300 cm with the water table in all columns maintained at 175 cm. After adding ammonium nitrate and irrigating, the peak in nitrate concentration moved downward to the 160‐cm depth, but nitrate concentrations decreased at 180 cm and almost disappeared at the 240‐ and 300‐cm depths. The soil solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…collections. Decreasing nitrate wii.h increasing depth had been documented in saturated lower profiles by Meek et al (1969Meek et al ( , 1970. Bicarbonate increased (cu = 0.01) with depth, presumably because of increased COz partial pressures (Boynton and Compton, 1944;McCall and Cole, 196S).…”
Section: Lysimeter Resultsmentioning
confidence: 93%
“…collections. Decreasing nitrate wii.h increasing depth had been documented in saturated lower profiles by Meek et al (1969Meek et al ( , 1970. Bicarbonate increased (cu = 0.01) with depth, presumably because of increased COz partial pressures (Boynton and Compton, 1944;McCall and Cole, 196S).…”
Section: Lysimeter Resultsmentioning
confidence: 93%
“…In the two soils that were tested, they calculated that more than sufficient soluble organic matter was leached with the nitrate to this zone to effect complete reduction of the nitrate. Similarly, Meek et al (1970) presented evidence of a continual drop in the redox potential from the surface to a 2 m depth at the tile drain. They showed that sufficient organic matter was leached with the drainage water to eventually reduce almost all of the nitrate throughout the profile.…”
Section: Agriculturementioning
confidence: 85%
“…Meek et al (1970) and Mansfeldt (2004 concentrations observed in the A and Ag horizons at the end of the unsaturated period (10 kPa pressure head step) may be the result of sample pre-treatment. Homogenization and air drying of the soil are likely to have promoted mineralization of organic N sources and caused the NO 3 − peak under unsaturated conditions.…”
Section: Trends Of Redox Potential and Arsenic In Response To Moisturmentioning
confidence: 99%